2019
DOI: 10.7762/cnr.2019.8.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistant Starch Supplementation on Glucose Metabolism, Lipid Profile, Lipid Peroxidation Marker, and Oxidative Stress in Overweight and Obese Adults: Randomized, Double-Blind, Crossover Trial

Abstract: Obesity is a substantial public health challenge across the globe. The use of resistant starch has been proposed as a probable management strategy for complications of obesity. We investigated the effects of resistant starch intake on lipid profiles, glucose metabolism, antioxidant status, lipid peroxidation marker, blood pressure, and anthropometric variables in subjects with overweight or obesity. In this 12-week, randomized, double-blind, placebocontrolled, 2 × 2 crossover trial, 21 Participants (mean age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…It has been found that RS intake reduces fat accumulation to improve insulin sensitivity, thereby maintaining blood glucose levels and lipid metabolic homeostasis ( 27 , 33 ). A human study confirmed that RSs significantly improved insulin and low-density lipoprotein cholesterol (LDL-C) levels in obese patients ( 34 ). Furthermore, supplementation of green bananas rich in RSs in NAFLD model mice was shown to improve SCFAs production and reduce hepatic steatosis by regulating the transporters involved in lipid excretion and adipogenesis ( 35 ).…”
Section: Therapeutic Potential Of Resistant Starches On Ameliorating ...mentioning
confidence: 89%
“…It has been found that RS intake reduces fat accumulation to improve insulin sensitivity, thereby maintaining blood glucose levels and lipid metabolic homeostasis ( 27 , 33 ). A human study confirmed that RSs significantly improved insulin and low-density lipoprotein cholesterol (LDL-C) levels in obese patients ( 34 ). Furthermore, supplementation of green bananas rich in RSs in NAFLD model mice was shown to improve SCFAs production and reduce hepatic steatosis by regulating the transporters involved in lipid excretion and adipogenesis ( 35 ).…”
Section: Therapeutic Potential Of Resistant Starches On Ameliorating ...mentioning
confidence: 89%
“…Resistant starch has been considered as a prebiotic and as a dietary strategy for the complications of obesity by reducing hyperinsulinemia and increasing the concentration of HDL-C [33], and by reducing fat accumulation. In fact, the group fed BB showed 26.6% less body fat than the group fed C, whereas the group fed BB + HF + S showed 57.7% less body fat than the group fed with C + HF + S. Interestingly, the groups fed with BB showed lower concentrations of serum leptin, insulin, glucose concentration and AUC after a glucose tolerance test than the group fed C, avoiding the postprandial glucose peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty consecutive obese children were recruited after obtaining written informed consent from their parents/guardians ( table 1 ). The sample size was based on a previous study on adults 9 and was done for pragmatic reasons in the absence of previous data from children.…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis of studies of RS on glucose metabolism, insulin, peptide YY (PYY), glucagon-like peptide 1 (GLP-1) and leptin in adults showed mixed results (partly on account of the mixed populations studied, the variable duration of studies, etc); they produced beneficial effects on glucose and insulin homeostasis and variable results on appetite-related hormones 8. The short-term response of gut hormones and satiety to RS containing meals has also been examined in adults and showed several beneficial changes 5 7 9 10. However, the short-term postprandial effects of RS on gut hormones and satiety have not been studied in children.…”
Section: Introductionmentioning
confidence: 99%